RESEARCH ON DYNAMIC SIMILARITY MODEL TEST OF DAMAGE DETECTION FOR TRANSMISSION TOWER - Zhou Ling; Li Ying-tao; Yang Chao-shan; Deng Zhi-ping; Chen Jin (Civil Engineering Journal, 2016)
In order to explore the dynamic similarity model test method different from atmospheric boundary layer wind tunnel and shaking table model test, in accordance with dynamic similar theory, an elastic model of a transmission tower with 1/35 scale and 5.2m height has been designed and manufactured with thin-walled circular pipes of high-density polyethylene. The model has been tested in the laboratory for time and frequency domain responses under suddenly unloading, essential dynamic characteristic of the scale model is also analysed and compared with that of its prototype tower, the dynamic similarity of the two is confirmed. By the mathematical deduction of Wigner-Ville Distribution (WVD) signal terms of structural free vibration response, the new damage detection index with clear physical signification is forwarded for damage detection for transmission tower, the damage detection test of the scale model of transmission tower is then carried out, totally three damage cases, related with chord rod weakening, flank rods failure, different damage degrees and positions, are tested to validate the proposed damage detection index.